Model Peningkatan Kinerja Pemasaran dan Keunggulan Bersaing UMKM melalui Peran Marketplace - Nurkhayati , Isnaini; Sulistiyani, Endang; Winarto; Indriasari, Febrina (Arden Jaya Publisher, 2025)
A thriving MSMEs sector is crucial to Indonesia's economic progress. According to statistics provided by the Indonesian Ministry of Cooperatives and Small and Medium Enterprises (Kemenkop UKM) (kemenkopukm.go.id/), 8.71 million MSMEs are expected to be operating in the country by 2022. Examine the relationship between micro, small, and medium-sized enterprises' (MSMEs) marketing effectiveness and competitive advantage as a function of the promotional mix. Supporting newly-established small and medium-sized enterprises (SMEs) in Indonesia is the primary goal of this research. The study sample consists of micro, small, and medium-sized enterprises (MSMEs) who have been actively involved in the marketplace's sales efforts for at least two years. We used SPSS Statics Version 25.0, a statistical program, to analyze the data. The independent variable, marketing performance, is significantly impacted by advertising, sales promotions, and personal selling. Personal selling, sales promotion, and advertising all have a mutually substantial impact on competitive advantage, the dependent variable. Keywords: competitive advantage, marketing performance, UMKM, marketplace, promotional mix